Opening the Dissertation: Overcoming Cultural Calcification and Agoraphobia - Denise Troll Covey (tripleC: Communication, Capitalism & Critique)
This article places the struggle to open access to the dissertation in the context of the crisis in doctoral education and the transition from print to digital literacy. It explores the underlying cultural calcification and agoraphobia that deter engagement with openness. Solving the problems will require overhauling the curriculum and conventions of doctoral education. Opening access to dissertations is an important first step, but insufficient to end the crisis. Only opening other dimensions of the dissertation – the structure, media, notion of authorship, and methods of assessment – can foster the digital literacy needed to save PhD programs from extinction. If higher education institutions invested heavily in remedying obsolete practices, the remedies would reverberate throughout the academy, accelerate advancement in the disciplines, and revolutionize scholarly publishing. The article ends with a discussion of the significant role librarians could play in facilitating needed changes given appropriate institutional commitment.